Sybil - Schreiber, Flora Rheta; Rosenman, Leonard 1924-2008 (Warner Home Video, 2006)
A landmark, classic drama depicting the extraordinary real life of a young woman suffering from multiple personality disorder. Includes the full 3-hour broadcast version (aired over two nights), along with over an hour of new exclusive special features
Orig.: USA 1976
Enth. Retrospective documentary: Examining Sybil ; Sybil thearpy session ; "The paintings of Sybil"